Faktor-Faktor Yang Mempengaruhi Produksi Tomat di Kelurahan Kawangu Kecamatan Pandawai Kabupaten Sumba Timur - Wadu, Junaedin (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 11 No 1 (2023): Maret, 2023)
Horticultural products such as tomatoes are complementary ingredients that must be met for many consumers because they are needed as a complement in making juice, chili sauce, and other industrial raw materials. In addition, the need for tomatoes is also increasing along with the increase in population and the number of culinary businesses at this time, so that tomato production needs attention. This study aims to analyze the factors that influence tomato production in Kawangu Village, Pandawai District, East Sumba Regency. The location selection was determined purposively with the consideration that Kawangu Village is one of the centers of tomato production in East Sumba Regency. The research method used in this study is a quantitative method with the number of respondents used in this study as many as 40 people who were taken randomly. The data analysis technique uses the Cobb-Douglas production function model in the form of the natural logarithm (ln). The results of this study indicate that the use of inputs such as land area and manure has a significant effect on tomato production, while other factors such as seeds, urea fertilizer, pesticides, and labor have no effect on tomato production in Kawangu Village.